A cooperative jamming technique to protect a two-user broadcast channel with confidential messages and an external eavesdropper - Anjos, Gustavo (2020)
This work addresses the security of a two-user broadcast channel. The challenge of protecting a broadcast channel is associated with the necessity of securing the system, not only against eavesdropping attacks originating from external nodes, but also to ensure that the inside users do not eavesdrop on each other’s information. To address this issue, the present work proposes a cooperative jamming scheme that provides protection against eavesdropping attacks carried out simultaneously by inside users and external eavesdroppers. To achieve this goal, the developed scheme combines real interference alignment with a blind cooperative jamming technique defined in the literature. An information theoretical analysis shows that positive secure degrees of freedom are achievable using the proposed solution.